2017
DOI: 10.1590/1678-992x-2016-0313
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and simultaneous selection gains for N-stress tolerance and N-use efficiency in maize tropical lines

Abstract: Maize plants can be N-use efficient or N-stress tolerant. The first have high yields in favorable environments but is drastically affected under stress conditions; whereas the second show satisfactory yields in stressful environments but only moderate ones under optimal conditions. In this context, our aim was to assess the possibility of selecting tropical maize lines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…The genetic material was composed of 906 maize single-crosses [22] obtained in a partial diallel using 49 of the 64 inbred lines studied in Morosini et al [18] (S1 Table). The 49 inbred lines were selected based on their nitrogen use efficiency [23] and identified as belonging from two heterotic groups, 35 flint and 15 dent [24]. Thorough study of the population of hybrids was previously reported [24,25].…”
Section: Phenotype Assessment and Analysismentioning
confidence: 99%
“…The genetic material was composed of 906 maize single-crosses [22] obtained in a partial diallel using 49 of the 64 inbred lines studied in Morosini et al [18] (S1 Table). The 49 inbred lines were selected based on their nitrogen use efficiency [23] and identified as belonging from two heterotic groups, 35 flint and 15 dent [24]. Thorough study of the population of hybrids was previously reported [24,25].…”
Section: Phenotype Assessment and Analysismentioning
confidence: 99%
“…In this study, we used the LNAE index (Low-N Agronomic Efficiency) to measure the tolerance of 64 tropical maize lines to low-N availability in the soil. In the LNAE index calculation, both the absolute GY at low-N availability and the ratio between low-N and optimum-N are considered [3,8]. Therefore, LNAE is an important index in maize breeding programs aimed at developing high-yielding cultivars even under low-N conditions.…”
Section: Discussionmentioning
confidence: 99%
“…N fertilization is expensive and also harmful to the environment because of the negative effect on water quality. In this context, the development of nutritionally efficient maize cultivars, which yield more with low fertilization, is a way to reduce fertilizer usage [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data was available for a total of 906 maize single-crosses derived from forty-nine inbred lines, contrast in the use of nitrogen [47], crossed in an unbalanced diallel mating design . Field trials were organized in an unreplicated augmented block design consisting of 47 (year 1) or 50 (year 2) blocks with 16 hybrids and two commercial checks evaluated in each block.…”
Section: Application To a Dataset Of Tropical Maize Hybrids Derived Fmentioning
confidence: 99%